-4b-2=2b-2b

Simple and best practice solution for -4b-2=2b-2b equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4b-2=2b-2b equation:


Simplifying
-4b + -2 = 2b + -2b

Reorder the terms:
-2 + -4b = 2b + -2b

Combine like terms: 2b + -2b = 0
-2 + -4b = 0

Solving
-2 + -4b = 0

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '2' to each side of the equation.
-2 + 2 + -4b = 0 + 2

Combine like terms: -2 + 2 = 0
0 + -4b = 0 + 2
-4b = 0 + 2

Combine like terms: 0 + 2 = 2
-4b = 2

Divide each side by '-4'.
b = -0.5

Simplifying
b = -0.5

See similar equations:

| 5x-4(x-7)=34 | | -7x+32=21 | | 4(y+3)=y+24 | | 2m+20=3m+8 | | 3r-1+r=2(1-2r) | | C+1.89=3.9 | | (8x^2/3)^3 | | Log(9x-8)=3 | | 0.66666666666(1+n)=-0.5n | | k+7=3+k+4 | | -3/4×17/3 | | X+2.6=5.4 | | b+7=1.78 | | 6(2x-3)+8=2(x+5) | | -1/2x=3/8 | | 3.8x=-19 | | -2v+4=16 | | 8m=4(5m+18) | | (16x-5x-1)-(4x+6)=4x+12 | | -10*-2.5p=5(10-0.5p*-10) | | 6x-36=x+74 | | 10*-2.5p=5(10-0.5p*10) | | 9x+3(4x)=84 | | 6(5a-b)-5(4b-7a)= | | 15(a-3)=-7-8 | | C+3.9=7.93 | | 4(x-2)=-3(2x-6) | | -8-12=11y-1-10y | | 5x+13y+18+3x-2y-20= | | 0.2(x-6)=0.3x+2+0.1 | | B+4.01=52 | | (w-3)w=346 |

Equations solver categories